Notch and Mean Stress Effect in Fatigue as Phenomena of Elasto-Plastic Inherent Multiaxiality - TAYLOR, DAVID (My University, 2011)
The present paper summarises an attempt of estimating fatigue lifetime of notched metallic materials by directly accounting for the degree of multiaxiality of the local elasto-plastic stress/strain fields acting on the fatigue process zone. In more detail, the proposed approach takes as its starting point the assumption that Stage I is the most important stage to be modelled to accurately estimate fatigue damage, and this holds true independently of the sharpness of the assessed geometrical feature. According to this initial idea, and by taking full advantage of the so-called Modified Manson-Coffin Curve Method (MMCCM), the hypothesis is then formed that the crack initiation plane is always coincident with that material plane experiencing the maximum shear strain amplitude. Subsequently, to devise an efficient design method capable of taking into account the detrimental effect of stress/strain gradients arising also from severe stress/strain concentration phenomena, the MMCCM is suggested here as being applied in terms of the Theory of Critical Distances (TCD), the latter being used in the form of the Point Method (PM). Further, in light of the well-known fact that the value of the mean stress/strain components in the vicinity of the stress/strain raisers? apices can be different from the corresponding nominal values due to the actual elasto-plastic behaviour of the material being assessed, it is shown, through the MMCCM itself, that also the mean stress effect can directly and accurately be treated as a problem of inherent multiaxiality. Finally, as a preliminary validation, the accuracy and reliability of the proposed approach is checked through several experimental results taken from the literature and generated by testing, under uniaxial fatigue loading, samples containing a variety of geometrical features, the effect of different nominal load ratios being investigated as well.
PUBLISHED
Keywords: Materials engineering; Theory of Critical Distances (TCD); Critical plane approach